THE STUDY OF THE RESULTS OF SURGICAL TREATMENT OF ARNOLD-CHIARI ANOMALY (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Arnold-Chiari anomaly (for the present time it calls anomaly of Chiari – AC) – is a congenital pathology of the rhombencephalon, presenting by the inadequacy of the posterior cranial fossa (PCF) and brain structures locating in that area which led to the ptosis of the brainstem and cerebellar tonsil to the great occipital foramen and incarceration of then on that level.